Rancang Bangun Pintu Geser Otomatis Menggunakan Sensor Ultrasonik Berbasis Mikrokontroler Atmega 328 - Wijaya; Asni Tafrikhatin; Prasetyo, David Andi (Politeknik Piksi Ganesha Indonesia, 2022)
Covid-19 is a pandemic that has occurred almost worldwide, especially in Indonesia. The spread of Covid-19 itself is very easy, such as direct contact with Covid-19 patients and objects exposed to the Covid-19 virus. This research aims to reduce the spread of the Covid-19 virus by creating an automatic sliding door using an ultrasonic sensor. This research method employs the Research and Development (R&D) approach. The design of this automatic sliding door utilizes an ultrasonic sensor, a stepper motor, and an Arduino Uno R3. The ultrasonic sensor detects objects in front of the door, which then automatically opens the door using a stepper motor as the driving mechanism. If the ultrasonic sensor does not detect any objects, the door will close automatically. It is hoped that this product can help reduce the spread of the Covid-19 virus.